Validation and reliability of the Timed Up and Go test for measuring objective functional impairment in patients with long‐standing rheumatoid arthritis: a cross‐sectional study. (5th December 2017) - Kojima, Toshihisa; Ishikawa, Hajime; Tanaka, Sakae; Haga, Nobuhiko; Nishida, Keiichiro; Yukioka, Masao; Hashimoto, Jun; Miyahara, Hisaaki; Niki, Yasuo; Kimura, Tomoatsu; Oda, Hiromi; Asai, Shuji; et al.
Abstract: Aim: This study aimed to validate the Timed Up and Go test (TUG) for measuring objective functional impairment in patients with established rheumatoid arthritis (RA) based on a prospective observational cohort of RA patients undergoing joint surgery. Methods: We collected data on demographics, Health Assessment Questionnaire Disability Index (HAQ‐DI), and associations between TUG and HAQ‐DI and other patient‐reported outcomes, including European Quality of life scale (EQ‐5D) were determined. Cut‐off values of TUG for HAQ remission (HAQ‐DI ≤0.5), normal HAQ (HAQ‐DI ≤0.25), and the absence of disability in each HAQ‐DI category were also determined by age. Results: A total of 435 patients were enrolled and analyzed. Mean age was 64.2 years, mean disease duration was 17.1 years, mean HAQ‐DI was 1.14, and mean TUG was 11.1 sec. TUG was significantly correlated with aging, EQ‐5D, and HAQ‐DI categories related to lower limb function (arising, walking, reach and activity). After adjusting for age and sex, mean TUG values were 9.0 sec (95% CI, 7.7–10.3) in patients with HAQ remission and 8.7 sec (7.4–10.4) in those with normal HAQ. By age, mean TUG values for HAQ remission were 7.2 sec (5.9–8.5) in young patients (≤61 years), 9.1 sec (7.6–10.5) in middle‐aged patients (62–70 years) and 10.0 sec (5.7–14.2) in old patients (≥71 years). Conclusion: TUG was significantly associated with functional impairment and aging in patients with long‐standing RA. Thus, TUG could be useful in setting treatment goals for joint surgery and rehabilitation in established RA patients.